2019
DOI: 10.21608/ajbs.2019.63997
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidant activities of Physalis peruviana and Hyphaene thebaica extracts

Abstract: Ethanol extract of Physalis peruviana and water extract of Hyphaene thebaica were tested for their inhibitory effects on eight bacterial strains (Escherichia coli, Proteus mirabilis, Salmonella typhimurium, Salmonella entrica , Shigella dysenteriae , Bacillus cereus, Bacillus licheniformis and Staphylococcus aureus) by using well diffusion technique. The study demonstrated that Staph. aureus was the most sensitive gram-positive strain and E. coli was the most sensitive gram-negative strain to ethanol extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our findings indicated that obese rats subjected to GB developed a decrement in the rheological alterations compared to untreated obese rats. The amelioration in rheological changes can be referred to as the direct effect of GB as an antioxidant elicited by lowering plasma TBARS and/or enhancing plasma GSH and SOD [44][45][46]. Ascorbic acid and phenolics found in GB fruit may participate in the high capacity of antioxidant level and high free radicals scavenging agent.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that obese rats subjected to GB developed a decrement in the rheological alterations compared to untreated obese rats. The amelioration in rheological changes can be referred to as the direct effect of GB as an antioxidant elicited by lowering plasma TBARS and/or enhancing plasma GSH and SOD [44][45][46]. Ascorbic acid and phenolics found in GB fruit may participate in the high capacity of antioxidant level and high free radicals scavenging agent.…”
Section: Discussionmentioning
confidence: 99%
“…Auwal et al [17] stated that the crude pericarp extract of Doum fruit exhibited broad-spectrum antibacterial activity Staphylococcus aureus, Streptococcus pyogenes, Salmonella typhi, Escherichia coli, and Shigella dysenteriae. Abd-ELmageed et al [18] mentioned that the ethanol extract of Doum fruit represented good different degrees of antibacterial activity against Escherichia coli, Salmonella typhimurium, Proteus mirabilis, Salmonella entrica , Shigella dysenteriae , Staphylococcus aureus, Bacillus cereus, and Bacillus licheniformis. On the other side, the current study disagrees with the results of Mohamed et al [19] which showed that methanolic extract of Doum has antifungal potential in addition to its antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Then, serial dilutions were transferred, one by one, to the respective wells. Plated were then incubated at 35 o C for 18 or up to 48 hours (for fungi). The MIC was considered as the lowest concentration which inhibited the growth of the The results of this analysis are listed as mean ± SEM (Standard Error of Means).…”
Section: Minimum Inhibitorymentioning
confidence: 99%